KEMANDIRIAN ANAK MELALUI SELF ACCESS CENTRE DALAM MENGEMBANGKAN TOP 10 SKILL - Wardani, Imas Srinana; Samsudin, Asep (Universitas Djuanda, 2019)
Education era 4.0 requires output that has top 10 skills 2020. One of the strategies needed in era 4.0 education is a Self Access Center (SAC) that focuses on children's self reliance in learning in elementary school. SAC is one of exploration of children's reliance independently in developing capabilities needed in the industrial era 4.0. The purpose of this study was to describe the reliance of children in learning an elementary school through a SAC in developing top 10 skills 2020. The method used in this study was descriptive qualitative. The results of the analysis show that the SAC can contribute. This is indicated by the achievement of the SAC has reached seven out of ten top skills, namely sense making, social intelegence, cross cultural competency, novel and adaptive thinking, transdiciplinary, computational thinking, and new media literacy and to be able to adjust to top 10 skills 2020 a better strategy is needed to achieve 10 skills with cognitive load management, design mindset and virtual collaboration.